COVID-19 therapy: from myths to reality and hopes - S. V. Bozrova; M. S. Drutskaya; S. A. Nedospasov (Медицинская иммунология, 2020)
The COVID-19 pandemic, caused by the SARS-CoV-2 coronavirus, is unprecedented for the 21st century and has already affected countries with a total population of billions of people. The number of infected has already surpassed 30 million people and the number of deaths has exceeded 1 million. Unfor-tunately, Russia is still one of the five countries with the largest number of infected people, although mortality from COVID-19 is significantly lower than in many other countries. Since the virus and the pathogenesis caused by it have a lot of new and unexpected features, high-tech and specific anti-viral drugs and vaccines have not yet been created. The most promising targets for future drug development are enzymes necessary for the life cycle of this particular virus (such as components of the replicase complex or viral proteases). Unexpected circumstances are pushing the evaluation of a number of previously developed and existing drugs directed toward other RNA viruses, some of which have already been shown effective in clinical trials against SARS-CoV-2. There is no doubt that soon prototypes of drugs of this class with higher specificity and effective-ness will be found. Another group of potential drugs are known drugs that are directed against various aspects of the pathogenesis caused by SARS-CoV-2, in particular, cytokine storm or coagulopathy. It should be emphasized that the genome of the virus encodes about 10 additional proteins, some of which may be related to unusual aspects of pathogenesis during COVID-19. Basic research should determine which of these proteins can be targets for specific therapy. Finally, the fact that neutralizing antibodies are found in the blood plasma of many patients and can be used for the prevention and treatment of COVID-19, indicates the potential of using recombinant neutralizing antibodies as drugs, and secondly, confirms the possibility of creating effective vaccines. This mini-review discusses therapeutic approaches and the status of clinical trials using drugs that already existed before the pandemic and were originally developed against other infectious agents or for the treatment of autoimmune pathologies. These drugs are part of today's arsenal in therapeutic protocols and are used in an attempt to cope with the COVID-19 epidemic in different countries.